Resíduos orgânicos em Cuiabá/MT : óbices para internalização de custos e reciclagem - Silva, Eliane Veltrudes Zanata Benedito da (2016)
Organic waste, when not disposed of properly, can lead to contamination of the environment. The populous cities often have difficulties in the integrated management of solid waste. The objective of this work was to indicate procedures to be adopted in order to identify the obstacles related to the costs of organic waste generation by economic agents classified as large generators in Cuiaba. Twelve establishments were surveyed, among the large organic waste generators, which were divided into three groups according to the characteristics of each agent, permanent fairs, wholesale supermarkets and wholesale vegetables and fruits companies. The research group generates approximately 50 tons of organic waste per day. Three types of method were used to investigate the results, quantitative, descriptive statistics and DAP; Exploratory and qualitative factorial analysis. The forms applied to economic agents were subdivided into these three areas. A questionnaire was also applied, and interviews with public agents, the data collected allowed to observe the governance of the agents. The results indicated that the economic agents try to socialize their negative externalities, pushing their responsibilities to third parties, this action was observed in the reviews of the DAP and exploratory factorial. With the qualitative data we verified the fragility of the institutional structure, vital for the reduction of the obstacles in the integrated management of organic wastes. It is concluded that the attitude of the agents to the problems that involve organic waste indicates to be successful in the management of organic waste, institutions must strengthen, to collect and regulate the regulatory framework that define the actions of economic agents. Consequently the integrated management of solid waste will be efficient.